Shopping Center: entre o lugar e o não-lugar - Bartoly, Flavio Sampaio (2009)
In the decade of 1940 in USA and in the years 60 in Brazil, probably, the affirmative that the shopping centers were less representatives for the everyday life and that the relation the public had with this spaces were very distant would not be contested. There were very little to do in a shopping center, because the administrations didn t get the potential of the shoppings in being more than a center where people would just buy things and with this, attract more people. Going to the mall was then unusual, quick and only for shopping. This first insertion of the shopping in the city, characterized as a place just for shopping, homogeneous, objective and little communicative, made this urban equipment as a possible example of what some authors would call non-place ; a standardized landscape, projected without take in consideration contexts or particular factors which could promote an identification with the people who are there. A space without peculiarities, a landscape without form, without soul, materialist (valuing spiritual and intellectual things too little) which reduces the communication to the minimum necessarily required by objectivity. This way one establishes a place, which by its own lack of authenticity, can t be reputed as a place. In a number of years, many factors contributed for the considerable modification of the shopping s insertion inside the city, even if the homogenized form and the main goal of the commerce are kept. The shopping became also a space of sociability, where people meet everyday, have fun and go for a walk. Despite we can qualify the shopping s sociability as instrumental (because it is an strategy of the administration in order to amplify the time people stay and buy), the sociability is an objective itself to the users. So we took the challenge of establish a discussion about the valuation of calling the shoppings of today as non places, especially when facing the everyday more deep relationship between the shopping and the users and with the city itself. Through its special organization, the search for a placed dimension of the shopping can give important contributions towards the comprehension of the aspects of the contemporary urban reality. With this objective, we made a bibliographic search, which provided us with the instruments to establish discussions about the conceptions of place, non-place and sociability, well as the possibility of a better comprehension of the insertion of the shopping in urban space. We collected also a number of data and used the participant observation in BarraShopping and Iguatemi Rio, well as made interviews with the administrations and users of these shoppings.